Pengembangan Wilayah Berbasis Sumber Daya Lokal di Wilayah Serang Studi Observasional di Kecamatan Tirtayasa dan Kecamatan Anyer, Kabupaten Serang - Malika Auliya Nurrin; Putri Yulianisa (STKIP Subang, 2025)
This study explores strategies for regional development based on local resources in Serang Regency through an observational study in Tirtayasa and Anyer Districts. The research applies a descriptive-qualitative approach using field observation, interviews, and secondary data analysis. The findings reveal that Tirtayasa has great potential in agriculture and fisheries, while Anyer excels in tourism. However, both areas face similar challenges, including limited infrastructure, low digital literacy among the community, and weak integration between local potentials and regional development policies. Moreover, a centralized development approach has limited community participation in planning and implementation processes. Therefore, a participatory, community-based development strategy that fully utilizes local resources is urgently needed. This study recommends a sustainable development model that emphasizes stakeholder collaboration, local economic empowerment, and digital transformation for community enterprises.